An update on the coronary calcium score: a review for clinicians - Monika Czaja-Ziółkowska; Jarosław Wasilewski; Mariusz Gąsior; Jan Głowacki (Advances in Interventional Cardiology, 2022)
The clinical manifestation of coronary artery atherosclerosis is coronary artery disease (CAD) with symptoms ranging from exertional chest pain due to reduction of coronary flow reserve to acute coronary syndrome due to rupture of usually a nonobstructive plaque with abrupt coronary blood flow reduction. CAD is the leading cause of morbidity and mortality worldwide. Therefore, identifying asymptomatic people at risk of CAD is pivotal to guide decision-making for primary prevention. Coronary artery calcium (CAC) is a hallmark of coronary artery atherosclerosis. It can be detected using cardiac computed tomography and quantified by the Agatston method. CAC examination is a cheap, fast and low radiation dose test, without injecting a contrast agent. It provides prognostic information over other traditional cardiovascular risk markers and established scoring systems, especially for low-risk subgroups such as women and younger adults, and indicates the appropriate moment to implement primary prevention, including acetylsalicylic acid and statins. In this review, we discuss the methods of CAC evaluation, the meaning of a zero CAC score (CACS), its conversion to CACS > 0 and the impact of this fact on cardiovascular risk, the effect of statins and proprotein convertase subtilisin/kexin type 9 inhibitor on CAC progression, interpretation of CACS results, and CACS prognostic value in both asymptomatic and symptomatic patients.